The effect of varying loading directions and loading levels on crack growth at 2D- and 3D-mixed-mode-loadings - A. Eberlein; H.A. Richard (Fracture and Structural Integrity)
While product’s operation the loading situation commonly changes. The local loading situation on an existing crack then can shift to a combined loading, composed of mode I, mode II and mode III, and consequently influence the product’s durability significantly. This influence on further fatigue crack growth and structures’ failure can be positive or negative. Present article describes and discusses the effect of varying loading directions from mode I- to 2D-mixed-mode-loading as well as from mode I- to mixedmode I + III-loading. Moreover, experiments on varying loading levels are performed by interspersing mixed-mode block loads in cyclic mode I base load, cyclic mode II base load as well as in cyclic mode III base load